Relationship between the serum GDF-15 concentration and muscle function in female patients receiving aortic valve replacement (TAVR, SAVR): Comparison with healthy elderly female subjects. (June 2022) - Fukuda, Taira; Nakajima, Toshiaki; Yazawa, Hiroko; Hirose, Suguru; Yokomachi, Jun; Kato, Takashi; Nishikawa, Riichi; Koshiji, Nobuo; Tokura, Michiaki; Nasuno, Takahisa; Nishino, Setsu; Obi, Syotaro; et al.
Abstract: Purpose: Sarcopenia is closely associated with postoperative prognosis in patients undergoing cardiovascular surgery. Growth differentiation factor (GDF)-15 is involved in the pathogenesis of cardiovascular disease. We examined the relationship between the serum GDF-15 concentration and muscle function in patients receiving aortic valve replacement and healthy elderly subjects. Methods: Forty-three female patients undergoing aortic valve surgery (79.9 ± 6.4 years; transcatheter aortic valve replacement [TAVR] n = 19, conventional surgical aortic valve replacement [SAVR] n = 24) and 64 healthy elderly female subjects (75.9 ± 6.1 years) were included. Walking speed, grip strength, and skeletal muscle mass index (SMI) by a multifrequency bioelectrical impedance analyzer were measured to determine the presence of sarcopenia. Preoperative serum GDF-15 concentration was measured by enzyme-linked immunosorbent assay. Results: The GDF-15 level was higher in patients receiving aortic valve replacement than in healthy elderly subjects (aortic valve replacement: 1624 ± 1186 pg/mL vs. healthy: 955 ± 368 pg/mL, p < 0.001). Multivariate linear regression analysis showed that the serum GDF-15 level determined grip strength independently of the high-sensitivity C-reactive protein level and eGFR, even after adjusting for age (β = -0.318, p = 0.025). Sarcopenia was found in 12.5% of healthy elderly subjects, 83.3% of patients with TAVR, and 64.3% of patients with SAVR. The GDF-15 concentration that defined sarcopenia was 1109 pg/mL in subjects including patients receiving aortic valve replacement. Conclusions: The preoperative serum GDF-15 concentration, which was higher in female patients receiving aortic valve replacement than in healthy elderly subjects, may be a serum marker of sarcopenia.